“Get Up and Heal Yourself!” Self-Enhancement Technologies and Sanctification - BIEHL, Michael (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2024)
This paper critiques the use of self-enhancement technologies through the lens of sanctification, avoiding a simplistic binary between affirmation and rejection. It examines the cultural fascination with self-tracking and optimization tools, which promise physical, mental, and spiritual improvement. By contrasting these technologies with theological concepts, the paper raises critical questions about their anthropological and spiritual assumptions. It highlights how these technologies perpetuate a reductionist view of the human self, rooted in data-driven self-regulation. The paper also critiques similarities between self-enhancement and transhumanist aspirations, pointing to their shared emphasis on control, efficiency, and self-perfection. A Christian theological response is proposed, emphasizing the transformative process of sanctification as an alternative to the performance-oriented paradigm of self-optimization. By engaging critically with the promises and limitations of self-enhancement tools, the paper advocates a nuanced understanding of human flourishing that respects the mystery and relationality inherent in Christian anthropology.